1993
DOI: 10.1021/np50094a005
|View full text |Cite
|
Sign up to set email alerts
|

A New Procedure for the Isolation of Anti-HIV Compounds (Polysaccharides and Polyphenols) from the Marine Alga Fucus vesiculosus

Abstract: Anti-HIV-active polysaccharides and polyphenols were isolated from the brown seaweed Fucus vesiculosus by hot H2O extraction of both the intact and the homogenized algae. This was followed by XAD2 chromatography and by sequential precipitation of the non-adsorbed compounds with glacial HOAc and thereafter with EtOH. The precipitate was solubilized, dialyzed against distilled H2O, and chromatographed on SP-Sephadex C25 and on QAE-Sephadex A25. This was followed by gel filtration on Sephadex G50 and Sephadex G10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(59 citation statements)
references
References 17 publications
(19 reference statements)
2
56
0
1
Order By: Relevance
“…All the six crude extracts in the current screening showed positive results in phenol-sulfuric acid reaction (data not shown), suggesting that the main effective components in these extracts were polysaccharides. As can be found in the literature, a number of polyanionic substances or water-soluble sulfated polysaccharides are potential antiviral agents (Béress et al, 1993;Ponce et al, 2003). It is commonly suggested that these negatively charged molecules disturb the proliferation cycle of enveloped viruses at the early stage, therefore inhibiting the viral infection (Witvrouw and de Clercq, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…All the six crude extracts in the current screening showed positive results in phenol-sulfuric acid reaction (data not shown), suggesting that the main effective components in these extracts were polysaccharides. As can be found in the literature, a number of polyanionic substances or water-soluble sulfated polysaccharides are potential antiviral agents (Béress et al, 1993;Ponce et al, 2003). It is commonly suggested that these negatively charged molecules disturb the proliferation cycle of enveloped viruses at the early stage, therefore inhibiting the viral infection (Witvrouw and de Clercq, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, they can be considered se lective inhibitors of herpesvirus replication. [7,13], whereas other marine-derived polysaccharides were also active against yel low fever virus and retroviruses [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Two commercial preparation of fucoidan, "Fucoidan fraction 7" supplied by Calbiochem, San Diego, California 18) termed F7 here, and a cruder preparation of fucoidan from Aberrant wound healing, either causing scarring or chronic wounds, is a significant cause of morbidity. There is therefore, considerable interest in agents which can modulate certain aspects of the wound healing process.…”
Section: Fibroblast Isolation and Culturementioning
confidence: 99%